Davčna kriminaliteta v teoriji in praksi (University of Maribor Press, 2017)
Tax Crime in Theory and Practice. Due to the damage it causes to state budgets and taxpayers, tax crime is often subject of intense discussions. Tax crime is transnational in its nature; it is not limited to a specific social status of perpetrators and requires the application of specific skills related to law and economy. In the course of tax crime investigations, investigators ask themselves whether a certain conduct actually constitutes a criminal offence or is it merely a business practice, which is also an approach frequently applied in the defence strategy of alleged perpetrators. As a result, tax crime detection and investigation, as well as the production of evidence in tax crime cases, represent an extremely complex set of actions and require multidisciplinary investigative approaches. The present monograph provides an insight into the tax crime phenomenon, the complexity of which is presented from theoretical and practical aspects. It explores topics related to the classification of (illicit) acts, the exchange of data, the application of criminal intelligence, the role of political actors and the issue of scientific research in this particular field.